THe EFFECT OF DHIKR JAHR THERAPY AS AN INTERVENTION TO REDUCE ANXIETY IN THE ELDERLY WITH HYPERTENSION - Rahayu, Arinda Tri; Ts. Fitriyah, Erna; Camelia, Dina; Wahdi, Achmad; Fatma Pratiwi, Tiara (Jurnal Insan Cendekia, 2024)
Introduction: Hypertension is referred to as "The Silent Killer" because most people have no symptoms until complications arise. Physical decline due to the aging process, symptoms of hypertension, and social environmental problems cause anxiety in the elderly. Jahr dhikr therapy can help reduce the level of anxiety and hypertension in the elderly. Objective: This study is to determine the effect of dhikr jahr therapy as an intervention to reduce anxiety in the elderly with hypertension. Methods: The research design uses case studies with nursing care methods. The subjects used in this study were 2 elderly patients who had hypertension with the nursing problem of anxiety, the study was conducted for 7 days using the intervention of dhikr jahr therapy. Results: There was a decrease in the level of anxiety and hypertension in the two elderly respondents after 7 days of jahr dhikr therapy with a duration of 10 minutes every day. Conclusion: So it can be concluded that there is an influence between reducing the level of anxiety and hypertension using jahr dhikr therapy in the elderly.